The great Gatsby - Fitzgerald, Scott 1896-1940. Francis Scott Key Fitzgerald (New Delhi : Prakash Books India Pvt. Ltd., 2022)
A young man, newly rich, tries to recapture the past and win back his former love, despite the fact that she is married.
b
Keywords: Fitzgerald, F. Scott -- 1896-1940.